Aortic rupture during transcatheter aortic valve replacement requiring emergent thoracic endovascular aortic repair and endograft infection requiring endograft explant - Ryan Wahidi, MD; Dan Kindell, MD; Puja Kachroo, MD; J.Westley Ohman, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
Infection of endografts after thoracic endovascular aortic repair (TEVAR) is a catastrophic complication with dramatically high morbidity and mortality. We present the case of a 58-year-old gentleman who underwent TEVAR for aortic rupture during transcatheter aortic valve replacement, later presenting with TEVAR infection, endocarditis, and aortobronchial fistula who underwent TEVAR explantation, aortic valve replacement, and aortic reconstruction. The patient consented to publication of his operative course.